faatan Layanan Kesehatan pada Peserta BPJS Kesehatan - Mustafidah, Malikhatul; Indrawati, Fitri (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2021)
The presentation of utilization health services of BPJS participants in Kendal Regency was still relatively low. That was influenced by the low participation coverage. The number of BPJS participants at 2017/2018 reached 64% of the target 95%. One of them was Pegandon Health Center at 19.2%. The purpose of the study was to determine the factors associated with utilization health services of BPJS. The research design used mixed methode. This type of research was observational analytic with cross sectional design. The sample was 122 used a purposive sampling technique. Data were analyzed using chi square test and logistic regression. Qualitative data was presented in narrative form. The research was conducted in November-December 2019. The results showed that age ((RP=1,24; 95% CI 1,21-73,3), and availability of facilities (RP=1,18; 95% CI=1,10-13,3) were related to the utilization health services for BPJS participants. Conclusion, availability of facilities was the most influential factor in the utilization of health services of BPJS participants. Keywords: BPJS, Visit, Utilization